Features of legal protection of low-income families in Ukraine under martial law - Farion-Melnyk , Antonina; Kolesnikov, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
Relevance of the study. The full-scale war in Ukraine has provoked an increase in the number of socially vulnerable populations, which actualizes the issue of legal protection of low-income families. The main problem is the inconsistency of subordinate regulatory legal acts with the requirements of legislation declaring social guarantees, and insufficient control over their compliance, which leads to the necessity of judicial protection of violated citizens' rights.The purpose of the study is to determine the practice of legal protection of low-income families in Ukraine as a factor in increasing the effectiveness of ensuring state-guaranteed social standards.Research methods. The work applies a complex of general scientific and special methods: systemic-structural analysis to study the mechanisms of social and legal protection; comparative legal method for analyzing international and national standards of social security; method of generalization of judicial practice to identify problems of execution of court decisions in social cases; statistical analysis to assess the scale of non-execution of court decisions.Research results. An analysis of terminological concepts was conducted and criteria for low-income status were defined. It was established that the jurisdictional mechanism provides for judicial and administrative procedures for protecting the violated rights of low-income families. The main reasons for non-execution of court decisions in social cases were identified: the ability of central executive bodies to manipulate legislative norms through ambiguous interpretation, which violates the principles of the rule of law. It is proposed to unify the approach to drafting court decisions with mandatory reflection of clear financial indicators of payments, establishment of execution deadlines, and determination of responsibility of officials for non-execution. The necessity of creating a single integrated electronic system for selecting possible benefits for low-income groups of the population is substantiated, which will function based on comparing the list of services and the register of recipients, using the capabilities of artificial intelligence as an electronic assistant.